THE CONCEPT OF "THE SYNERGY OF INDONESIA RATTAN" AT THE INTERIOR DESIGN OF NATIONAL RATTAN INNOVATION CENTER (PIRNas) BY USING DESIGN THINKING METHOD - Zulyo Kumara Pratama (Ars: Jurnal Seni Rupa dan Desain, 2019)
As an effort to support the national rattan industry development through appropriate innovations, the government established the National Rattan Innovation Center (PIRNas) in Palu, Central Sulawesi in 2012. However as an important institution in the rattan development industry in Indonesia, there are a number of fundamental problems related to the interior design of the PIRNas that must be fixed. The PIRNas interior design uses design thinking methods (Bob Gill 2004). The interior design result of the PIRNas will focus on strengthening the concept and the story of "The Synergy of Indonesia Rattan" adapted from big attention and appreciation of the rattan travel values, mainly its history, process and national rattan potential. The designer applies rattan material with all room elements that complementary and continuous each other in applying the concept. The implementation is expected to present a strong image in representing the identity and role of the PIRNas as a national center for rattan research and its development.